A Pragmatic Analysis of Interjections in the Wild Child Movie: Types and Functions - Essie Setianingtyas Yuniardi; Widhiyanto (Journal of English Language Learning, 2025)
Language plays an essential role in human communication. Human communication itself involves the exchange and negotiation of thoughts and information. In general, sometimes people encounter difficulties in expressing their feelings and emotions, and this is where interjections serve as essential linguistic tools. This study investigates the types and pragmatic functions of interjections in the Wild Child movie, using the framework from Ameka (1992) to identify how they are used in the movie. The film was selected due to its rich intentional use of colloquial language and reflects authentic teenage communication. Using a descriptive qualitative approach, this study analysed the movie script categorized as interjections by grouping them into two main types, primary and secondary, and then identifying their pragmatic functions, such as emotive, cognitive, conative, and phatic. This proposes that interjections in the movie function not only as tools to help express emotions but also to manage interaction, maintain social bonds, and convey mental states. The study confirms that interjections' function depends on the context, regardless of their form. These insights support a deeper understanding of pragmatic language use features and emphasize the educational value of interjections in improving learners’ communicative competence.